2016
DOI: 10.1007/s10518-016-0053-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical analysis of an industrial RC tower

Abstract: This study presents the results of analyses performed using a dynamic 3D model of a RC skip tower located at a coal mine in Poland. Kinematic excitation was based on acceleration records of a mining tremor (underground mining activity) and an earthquake. Although Poland is not a particularly active seismic region, there are regional seismic phenomena associated with mineral exploitation. These vibrations, generally connected with human activity, are so-called paraseismic events. Whilst mining-related surface v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The error of the measured accelerations did not exceed 11.61%. The details of the measurement method have been described in the paper by Tatara et al (2017).…”
Section: Natural Frequencies Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The error of the measured accelerations did not exceed 11.61%. The details of the measurement method have been described in the paper by Tatara et al (2017).…”
Section: Natural Frequencies Of the Modelmentioning
confidence: 99%
“…Such a value of magnitude can be comparable with weak earthquakes. There are however many differences between earthquakes and mining tremors (Tatara et al 2017). The major differences are:…”
Section: Introductionmentioning
confidence: 99%
“…In highrise buildings located in the urban areas of many countries, wind-induced vibrations could have a significant influence on the structures [10]. In the Silesian region of Poland, mining excitation also occurs [20]. Irrespective of the source of excitation, vibrations in buildings could be annoying for residents.…”
Section: Introductionmentioning
confidence: 99%
“…The studies of damages of civil engineering structures caused by seismic as well as paraseismic loading have revealed that the protection of these structures turned out to be a problematic technical task [4]. Especially for footbridges erected on seismic activity areas, the dynamic loading caused by an earthquake occurs one of the most destructive issues [3].…”
Section: Introductionmentioning
confidence: 99%